The association of insulin resistance measured through the estimated glucose disposal rate with predictors of micro-and macrovascular complications in patients with type 1 diabetes. Issue 6 (December 2022) - Karamanakos, Georgios; Barmpagianni, Aikaterini; Kapelios, Christos J.; Kountouri, Aikaterini; Bonou, Maria; Makrilakis, Konstantinos; Lambadiari, Vaia; Barbetseas, John; Liatis, Stavros
Abstract: Background and aim: Insulin resistance (IR) is associated with a higher rate of type 1 diabetes (T1D) complications. We aimed to examine the relationship between estimated glucose disposal rate (eGDR), a readily available marker of IR in clinical practice and early predictor biomarkers of macrovascular and microvascular complications in patients with T1D. Design: A cross-sectional study. Methods: A total of 165 consecutive patients with T1D free of cardiovascular, eye, and renal complications were included in the study from 2016 to 2020. Participants were characterized as insulin resistant if their eGDR value was ≤ 8 mg/kg/min. Pulse wave velocity (PWV) and global longitudinal strain (GLS) were used as surrogates for subclinical atherosclerosis and left ventricular systolic dysfunction (LVSD), respectively. Four previously standardized tests based on the calculation of heart rate variability (HRV) were used to evaluate subclinical cardiac autonomic neuropathy (CAN). Early nephropathy was assessed by assessing urinary albumin to creatinine ratio (ACR). Results: The population sample (n = 165) included a majority of female patients (63%) and had a median age of 32 years (24−43), median disease duration of 14 years ( ± 9.5–21.5), a median BMI value of 23.7 kg/m 2 (21.4–26.6), an HbA1C of 7.2% (6.7–8.2) and median eGDR (lower values indicate higher insulin resistance) of 9.2 mg/kg/min (8.2–9.9), while 21.8% (n = 36) of the participants were characterized as insulin resistant. After adjustment for age, gender, and the duration of diabetes, the presence of IR was significantly associated with higher prevalence of subclinical atherosclerosis (OR:2.59, 95% CI: 1.06–6.30, p = 0.036), CAN (OR:3.07, 95% CI: 1.02–9.32, p = 0.047) and subclinical LVSD (OR: 4.9, 95% CI: 1.94–12.79, p = 0.001). No association was shown with ACR. Conclusions: In patients with T1D, insulin resistance, as measured by eGDR, correlates well with early CVD predictors and CAN. These associations appear independent of the effects of gender, aging, and disease duration. Highlights: The estimated glucose disposal rate (eGDR) may quantify insulin resistance. Insulin resistance is associated with an increased incidence of cardiovascular disease in type 1 diabetes. The eGDR correlates with cardiovascular predictors; an additional target in preventing type 1 diabetes complications.